Cerebral Circulation Updates on Models, Diagnostics and Treatments of Related Diseases - Scerrati, Alba; Ricciardi, Luca; Dones, Flavia (IntechOpen, 2022)
Diagnostics and diseases related to the cerebrovascular system are constantly evolving and updating. 3D augmented reality or quantification of cerebral perfusion are becoming important diagnostic tools in daily practice and the role of the cerebral venous system is being constantly revised considering new theories such as that of "the glymphatic system." This book provides updates on models, diagnosis, and treatment of diseases of the cerebrovascular system.